First-Principles Insight into the Structural and Electronic Properties of Metronidazole and Tinidazole - Sharma, Sagar; Khanal , Kamal (Butwal Campus Journal, 2025)
Metronidazole and tinidazole are among the most significant nitroimidazole antibiotics, essential for treating anaerobic bacterial and protozoal infections. These two drugs were studied using DFT at the B3LYP/6-31 G (d,p) level, as implemented in Gaussian 16W, for all major quantum mechanical calculations. Tinidazole (Egap = 4.60 eV) was found to be somewhat more stable than metronidazole (Egap = 4.58 eV), with a small difference in their energy gap. The DOS spectra validated the results of FMO analysis. Tinidazole, with a slightly higher electrophilicity of 5.07 eV compared to metronidazole's 4.86 eV, was observed to be a stronger electrophile. The Mulliken atomic charges and MEP surface analysis explained the difference in charge distribution and attack sites due to structural differences. The UV-Vis absorption spectra showed stronger absorption intensity in tinidazole compared to metronidazole, even though both exhibit similar spectral patterns, which is due to the presence of the ethylsulphonylethyl side chain in tinidazole. The FT-Raman spectra were almost similar for both drugs, while we observed some higher peaks in tinidazole than in metronidazole in the FT-IR spectra. The NCI-RDG analysis showed stronger van der Waals interactions and stronger steric repulsive effects in tinidazole than in metronidazole.